Occurrence of Campylobacter, Salmonella, and Arcobacter in pet birds of northern Iran - SEIFI, S.; KHOSHBAKHT, R.; AZIZPOUR, A. (Journal of the Hellenic Veterinary Medical Society, 2020)
Pet birds can harbor human pathogens and contribute to the transmission of infectious agents to human. Since many people are interested in keeping pet birds, this study was conducted in pet birds from Mazandaran province, northern Iran. Totally, 174 fecal samples of pet birds (cockatiel, canary, lovebird, parrot, mynah, goldfinch, budgerigar, macaw, dove, pigeon, and bulbul) were collected with sterile cotton swabs and submitted to Faculty ofVeterinary Medicine, Department of Pathobiology (Amol, Iran). After extraction of total DNA, the samples subjected to molecular detection of the Campylobacter, Salmonella, and Arcobacter using polymerase chain reaction. A total of 114 (65.5%), 28 (16%), and 86 (49.4%) samples were found positive for Campylobacter, Salmonella, and Arcobacter, respectively. Furthermore, some birds showed contamination with two or all three of these bacteria. Results showed that mentioned bacteria can be detected from the apparently healthy pet birds. Therefore pet birds can be considered as potential carriers of these enteropathogens.